Auxin Produced by the Indole-3-Pyruvic Acid Pathway Regulates Development and Gemmae Dormancy in the Liverwort Marchantia polymorpha . Issue 6 (2nd June 2015) - Eklund, D. Magnus; Ishizaki, Kimitsune; Flores-Sandoval, Eduardo; Kikuchi, Saya; Takebayashi, Yumiko; Tsukamoto, Shigeyuki; Hirakawa, Yuki; Nonomura, Maiko; Kato, Hirotaka; Kouno, Masaru; Bhalerao, Rishikesh P.; Lagercrantz, Ulf; et al.
Abstract : Auxin, which is synthesized in the liverwort Marchantia polymorpha via the smallest known toolkit among land plants, plays critical roles in development and dormancy of the gametophyte generation. Abstract: The plant hormone auxin (indole-3-acetic acid [IAA ]) has previously been suggested to regulate diverse forms of dormancy in both seed plants and liverworts. Here, we use loss- and gain-of-function alleles for auxin synthesis- and signaling-related genes, as well as pharmacological approaches, to study how auxin regulates development and dormancy in the gametophyte generation of the liverwort Marchantia polymorpha . We found that M. polymorpha possess the smallest known toolkit for the indole-3-pyruvic acid (IPyA ) pathway in any land plant and that this auxin synthesis pathway mainly is active in meristematic regions of the thallus. Previously a Trp-independent auxin synthesis pathway has been suggested to produce a majority of IAA in bryophytes. Our results indicate that the Trp-dependent IPyA pathway produces IAA that is essential for proper development of the gametophyte thallus of M. polymorpha . Furthermore, we show that dormancy of gemmae is positively regulated by auxin synthesized by the IPyA pathway in the apex of the thallus. Our results indicate that auxin synthesis, transport, and signaling, in addition to its role in growth and development, have a critical role in regulation of gemmae dormancy in M. polymorpha .